Pengaruh Advertising Disclosure Language terhadap Minat Beli Produk Beauty and Fashion di Instagram dengan Source Credibility sebagai Variabel Intervening - Keisia Christea; Puspita Chairun Nisa (IPB University, 2022)
Influencer marketing is a form of advertising in which the paid relationship between marketers and sponsors is not very clear. This relationship is clarified using advertising disclosure to protect consumer rights. The research investigates the influence of advertising disclosure on the sub-dimensional credibility of the source, namely attractiveness, expertise, and trustworthiness, as well as its direct and indirect influence on purchase intentions. The PLS-SEM analysis used data obtained from Instagram users aged 18-34 in Bekasi and Jakarta, had previously expressed an interest in buying beauty and fashion category products promoted by influencers on Instagram. The findings revealed that advertising disclosure significantly increases the sub-dimensional credibility of the source. Then, expertise and trustworthiness significantly increase purchase intentions; and the existence of advertising disclosure has a positive influence on the purchase intentions of beauty and fashion consumers on Instagram, both directly and indirectly. The findings further revealed that attractiveness had no effect on the purchase intentions of beauty and fashion consumers on Instagram. However, attractiveness, along with expertise and trustworthiness, can help influencer marketing be more effective. Overall, the study contributed to the literature on product endorsement by demonstrating how the influence of social media and ad disclosure can effectively improve consumer purchase intention on Instagram.